2021
DOI: 10.1021/jacs.0c10053
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Transfer Catalytic Activity in De Novo Designed Protein with N-Terminus of α-Helix As Oxyanion-Binding Site

Abstract: The design of catalytic proteins with functional sites capable of specific chemistry is gaining momentum and a number of artificial enzymes have recently been reported, including hydrolases, oxidoreductases, retro-aldolases, and others. Our goal is to develop a peptide ligase for robust catalysis of amide bond formation that possesses no stringent restrictions to the amino acid composition at the ligation junction. We report here the successful completion of the first step in this long-term project by building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…141 Degrado's group recently showed that three-helix bundles formed by domain-swapped 48-residue dimers (DSDs) can be designed as catalysts containing oxyanion-binding sites which were active in acyl transfer reactions such as peptide ligation through transthioesterification and aminolysis. 142 The heteromeric dimers contain pairs of peptides bearing complementary E or R residues, the anionic peptide being functionalized with an active cysteine residue near its N-terminus to facilitate the reaction with a peptide-α thioester substrate.…”
Section: Catalysts Based On Helical Constructsmentioning
confidence: 99%
“…141 Degrado's group recently showed that three-helix bundles formed by domain-swapped 48-residue dimers (DSDs) can be designed as catalysts containing oxyanion-binding sites which were active in acyl transfer reactions such as peptide ligation through transthioesterification and aminolysis. 142 The heteromeric dimers contain pairs of peptides bearing complementary E or R residues, the anionic peptide being functionalized with an active cysteine residue near its N-terminus to facilitate the reaction with a peptide-α thioester substrate.…”
Section: Catalysts Based On Helical Constructsmentioning
confidence: 99%
“…Breaking the symmetry of de novo CC homo-oligomers to make heteromeric systems has many advantages and potential applications. 37, 52, 76 We sought to expand the utility of apCC-Tet* by redesigning it to make an A2B2 heterotetramer, apCC-Tet*-A 2 B 2 . For this, we maintained the g, a, d and e sites as Gln, Leu, Ile, and Ala, respectively, and made two potentially complementary peptides: an acidic peptide, apCC-Tet*-A, with Glu at all b and c positions; and a basic peptide, apCC-Tet*-B, with Lys at those sites.…”
Section: Resultsmentioning
confidence: 99%
“…Breaking the symmetry of de novo CC homo-oligomers to make heteromeric systems has many advantages and potential applications. 37,52,76 We sought to expand the utility of 1 and S2). The four peptides were synthesized by SPPS, purified, verified by mass spectrometry (Figures S23-S26), and characterized alone and as equimolar paired mixtures as follows.…”
Section: Apcc-tet* Can Be Adapted To Build Antiparallel Heterotetramersmentioning
confidence: 99%
“…The practice of enzymatic peptide ligation for protein synthesis and protein tagging began with the engineering of subtiligase in the 1990s, which also witnessed the original development of chemical ligation methods that operate in water. Subtiligase and its variants are engineered from bacterial proteases (i.e., subtilisins) and catalyze the aminolysis of an ester or thioester substrate for peptide bond formation. Most recently, de novo proteins were designed to catalyze the acyl transfer reaction of peptide thioesters for aminolysis, representing a promising initial step toward the development of artificial peptide ligases . In contrast, naturally occurring peptide ligases such as sortase A and PALs effect peptide ligation through catalyzing the transpeptidation reaction of straight peptide or protein substrates.…”
Section: Discussionmentioning
confidence: 99%
“…60−63 Most recently, de novo proteins were designed to catalyze the acyl transfer reaction of peptide thioesters for aminolysis, representing a promising initial step toward the development of artificial peptide ligases. 64 In contrast, naturally occurring peptide ligases such as sortase A 65 and PALs effect peptide ligation through catalyzing the transpeptidation reaction of straight peptide or protein substrates. With their extremely high catalytic activity toward P1-Asn substrates, PALs are the most powerful peptide ligases known to date.…”
Section: ■ Conclusionmentioning
confidence: 99%